Psychological diagnostic of risk factors for involving adolescents in the use of narcotic substances: the development of a methodical complex. Part 1. Scale structure and psychometric characteristics - E. G. Demenko; E. I. Rasskazova; A. Sh. Tkhostov; E. A. Brun; B. V. Arshinova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Paper  is  devoted  to  the  development  and  validation  of  the  methodological  complex  for psychological  diagnostic  of  the  risk  factors  for  involving  adolescents  in  the  use  of  narcotic  substances.  The diagnostic of people using psychoactive substances is difficult due to their defensive strategy of answers — both because  of  the  intentional  desire  to  keep  their  behavior  in  secret,  and  because  of  distortion  of  the  assessment of Self and own behavior. An expanded clinical-psychological observation, due to its high costs, is not always possible, which makes it urgent to develop a primary screening instruments, on the basis of which it is possible to identify risk groups for whom the clinical-psychological examination is especially important, controlling for possible falsifications in the responses. In this work three psychodiagnostic approaches are consistently applied to  overcome  these  difficulties:  after  the  initial  theoretical  development  of  constructs,  items  are  selected  based on  “empirical  keying”  approach  (by  their  ability  to  differentiate  the  clinical  and  control  groups),  and  then scales  are  refined  based  on  their  psychometric  characteristics  in  the  clinical  not  a  control  group.  This  first part of the paper presents the results of testing consistency and factor validity of the methodological complex scales conducted on a sample of 637 pupils of the upper grades of general education schools from 12 subjects of  the  Russian  Federation  and  108  pupils  involved  in  the  use  of  narcotic  substances.  The  methodological complex  includes  scales  of  technological  addictions,  antisocial  tendencies,  self-regulation,  emotional  control, novelty  seeking,  risky  behavior,  child-parent  relations,  coping  strategies  for  problem  solving,  social  support and  avoidance,  as  well  as  additional  indicators  of  socially  desirable  and  random  answers.